Ameliorative Role of Cerium Oxide Nanoparticles Against Fipronil Impact on Brain Function, Oxidative Stress, and Apoptotic Cascades in Albino Rats - Elshony, Norhan; Nassar, Atef M. K.; El-Sayed, Yasser S.; Samak, Dalia; Noreldin, Ahmed; Wasef, Lamiaa; Saleh, Hamida; Elewa, Yaser H. A.; Tawfeek, Shereen E.; Saati, Abdullah A.; Batiha, Gaber El-Saber; Tomczyk, Michał; et al. (Frontiers in Neuroscience, 2021)
Abstract: Fipronil (FPN) is an N-phenylpyrazole insecticide that is used extensively in public health and agriculture. These exposures are linked to negative health outcomes toward humans and animals. It has been stated that exposure to FPN prompted neuronal cell injury, which results in apoptosis through the production of reactive oxygen species (ROS). Consequently, the purpose of the current study was to investigate the neuroprotective effects of CeNPs on neuronal dysfunction induced by FPN in albino rats. Male rats were randomly classified into four groups: control, FPN (5 mg/kg bwt), CeNPs (35 mg/kg bwt), and FPN + CeNPs (5 (FPN) +35 (CeNPs) mg/kg bwt), which were treated orally once daily for 28 consecutive days. Brain antioxidant parameters, histopathology, and mRNA expression of genes related to brain function were evaluated. The current study revealed oxidative damage to brain tissues in FPN-treated rats indicated by elevated levels of malondialdehyde (MDA) and nitric oxide (NO) and reduced activities of antioxidant enzymes superoxide dismutase (SOD) and glutathione peroxidase (GPx). In addition, FPN treated rats showed decreased butyrylcholinesterase (BuChE) activity. Moreover, FPN up-regulated the expression of Neuron-specific enolase (NSE), Caspase 3, and Glial fibrillary acidic protein (GFAP) but down-regulated B-cell lymphoma-2 (BCL-2) expression. Histopathological examination of the FPN treated group reveals clear degenerative lesions in brain tissue. Immunohistochemically of brain tissues of rats treated with FPN showed abundant ionized calcium-binding adaptor molecule 1 (Iba-1) microglia and Caspase3 and apoptotic cells with nearly negative calbindin and synaptophysin reaction. The CeNPs counteracted the neurotoxic effect of FPN exposure by antioxidant-mediated mechanism. Therefore, this study suggested an ameliorative effect of CeNPs against FIP-induced neurotoxicity.